2002
DOI: 10.1159/000064259
|View full text |Cite
|
Sign up to set email alerts
|

Murine AIDS Induces Viremia and Functional and Phenotypic Alterations in Blood Cells

Abstract: Background: Murine acquired immunodeficiency syndrome (MAIDS) is characterized by generalized lymphoproliferation and progressive immunodeficiency. It is induced by a mixture of two replication-competent murine leukemia viruses (MuLV) and a disease-causing, replication-incompetent defective MuLV. Infection leads to specific phenotypic and functional alterations of lymphocytes in lymphoid organs. Methods: We analyzed phenotypic, virological and functional parameters in the blood of mice infected with MAIDS viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…We found no significant increase of LP-BM5 copy numbers as detected by cPCR over time (data not shown). LP-BM5-induced TH2 lymphocyte function is rapid and sustained until the death of the mouse (17,20,28,47,58). We have reported that ventricular dilation and decreased ␤ occurs in the absence of cardiac lymphocytic infiltrates and inflammatory mediators (4,40).…”
Section: H647mentioning
confidence: 97%
See 1 more Smart Citation
“…We found no significant increase of LP-BM5 copy numbers as detected by cPCR over time (data not shown). LP-BM5-induced TH2 lymphocyte function is rapid and sustained until the death of the mouse (17,20,28,47,58). We have reported that ventricular dilation and decreased ␤ occurs in the absence of cardiac lymphocytic infiltrates and inflammatory mediators (4,40).…”
Section: H647mentioning
confidence: 97%
“…The LP-BM5 retrovirus mixture was administered intraperitoneally to mice in 0.1 ml of minimum essential medium with an esotropic titer of 4.5 log 10 plaque-forming units ϫ 10 Ϫ3 /l, which induces TH2 dominant lymphocyte function comparable with that previously published (17,20,47,58). The mice were infected with LP-BM5 2 wk before treatment with the TCR-V␤ peptides, as done previously in earlier studies (27,40,49).…”
Section: Lp-bm5 Viral Infectionmentioning
confidence: 97%